Sistem Informasi Prediksi Jurusan Perguruan Tinggi Dengan Metode K-Nearest Neighbour - , (Seminar Nasional Informatika (SENATIKA), 2021)
Along with the development of information technology brings influence to the world of education, because more and more technologies are emerging making many people now dependent on technology is no exception students and students Witama National Plus..Every new school year many students and students who enter a college are not based on their abilities, talents and interests, resulting in mistakes in the determination of majors. Knn method is a method in artificial intelligence science that can help calculate the proximity of calculation results with samples already provided in the database that will produce information according to the current conditions. With the information system of determining college majors using the K-Nearest Neighbour method makes it easy to determine the majors that match the criteria owned by prospective graduates of Witama High School so that they get a major that matches the selected criteria